2021
DOI: 10.1101/2021.07.05.451214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling niche theory and beta diversity change

Abstract: Beta diversity describes the differences in species composition among communities. Changes in beta diversity over time are thought to be due to selection based on species' niche characteristics. For example, theory predicts that selection that favours habitat specialists will increase beta diversity. In practice, ecologists struggle to predict how beta diversity changes. To remedy this problem, we propose a novel solution that formally measures selection's effects on beta diversity. Using the Price equation, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…Temporal partitioning of Hill-number-based beta diversity could thus give us a synthetic understanding of community dynamics. Exploring the potential connections between our method and other partitioning methods that are based on Hill numbers (Godsoe et al, 2021(Godsoe et al, , 2022 would also be an important way forward.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal partitioning of Hill-number-based beta diversity could thus give us a synthetic understanding of community dynamics. Exploring the potential connections between our method and other partitioning methods that are based on Hill numbers (Godsoe et al, 2021(Godsoe et al, , 2022 would also be an important way forward.…”
Section: Discussionmentioning
confidence: 99%
“…This approach outlines each of the mechanisms described in (Vellend 2010) can be analysed, including speciation, drift and immigration. Extensions to Hill numbers and beta diversity can be found in (Frank and Godsoe 2020; Godsoe et al 2022). Though the development of partitions for diversity change are relatively recent, these techniques draw on a rich literature of partition methods developed for other problems in ecology and evolution (Collins and Gardner 2009; Fox 2016; Loreau and Hector 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Vellend’s framework emphasizes conceptual insights, but several authors have proposed empirical approaches inspired by this insight. For example, Godsoe et al (2022) showed how models of selection could be used to analyse changes in Shannon diversity at multiple spatial scales, while Tatsumi et al (2021)analysed changes in measures of diversity related to species richness. Though these approaches show promise we currently lack the ability to explicitly compare these explicit and implicit models of biotic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal partitioning of Hill-number-based beta diversity could thus give us a synthetic understanding of community dynamics. Exploring the potential connections between our method and other partitioning methods that are based on Hill numbers (Godsoe et al, 2021(Godsoe et al, , 2022 would also be an important step forward.…”
Section: Discussionmentioning
confidence: 99%